Preparation method of ferroelectric nanoparticles with surfaces rich in grain boundary and torsional strain
Through the surface of the bismuth manganate ferroelectric nanoparticles with grain boundaries and torsional strain, ultrasound-induced polarization reversal is used to solve the problem of insufficient endogenous hydrogen peroxide in tumor treatment, significantly improving the catalytic efficiency and the generation of reactive oxygen species, and enhancing the anti-tumor treatment effect.
Patent Information
- Application Number
- CN202411751558.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
Existing nanoenzymes rely on tumor endogenous hydrogen peroxide in tumor treatment, resulting in insufficiency of catalytic efficiency.
Using ferroelectric nanoparticles with grain boundaries and torsional strain on the surface, polarization inversion and charge separation are induced by ultrasound, catalytic reactions are enhanced and water and oxygen are promoted to convert to hydrogen peroxide.
Under ultrasonic conditions, bismuth manganate nanoparticles significantly accelerate the water oxidation reaction, generating abundant hydrogen peroxide, supplementing the insufficient hydrogen peroxide in the tumor microenvironment, amplifying the production of reactive oxygen species, and enhancing the anti-tumor treatment effect.
Smart Images

Figure CN119569124A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing ultrasonically responsive ferroelectric nanoparticles. Background Art
[0002] Currently, most nanomedicines are designed to catalyze the release of hydrogen peroxide (H 2 O 2 ) generate reactive oxygen species (ROS) to induce tumor ablation. 2 O 2 The concentration of (10μM~100μM) is higher than that of normal tissues (0.1μM~1μM), but it is still insufficient to meet the substrate requirements of enzyme-catalyzed reactions, especially those involving Fenton chemistry (100μM~1000μM). Recently, nanomaterials with perovskite structures have demonstrated excellent electrocatalytic and enzyme-like catalytic properties. The perovskite structure is characterized by high crystal stability, tunable chemical composition, and excellent electrical conductivity, which together enhance its catalytic performance in oxygen reduction reaction (ORR) and water oxidation reaction (WOR). These properties enable these nanomaterials to effectively promote electron transfer and improve reaction efficiency, especially in the WOR / ORR process, where they help to generate hydrogen, such as H 2 O 2 However, the slow kinetics of WOR and ORR itself remains a major obstacle to improving the catalytic efficiency of perovskite-based materials.
[0003] In recent years, advances in ferroelectric crystalline materials have provided promising solutions to these challenges. These advances have successfully overcome the inherent kinetic limitations of water splitting and significantly accelerated the WOR and ORR processes by utilizing ultrasound-induced polarization reversal and charge separation to enhance catalytic reactions. With the help of their electromechanical properties, ferroelectric materials are able to achieve reversible transformation of mechanical energy through dynamic changes in polarization and electrical domains. Therefore, due to their unique properties, these materials can be effectively used as sonosensitizers, and their properties are affected by multiple factors, especially point defects and line defects. Doping with foreign elements is a widely adopted strategy to change the electronic structure, which can improve the chemical stability and catalytic performance of materials in acidic TMEs. However, excessive point defects can destroy the crystal structure and ferroelectric domain behavior, thereby weakening the ferroelectric response; similarly, line defects such as dislocations can significantly affect the polarization reversal of ferroelectric domains. Summary of the invention
[0004] The present invention aims to solve the problem that existing nanozymes rely on endogenous hydrogen peroxide in tumor treatment, and further provides a method for preparing ferroelectric nanoparticles with rich grain boundaries and torsional strain on the surface.
[0005] A method for preparing ferroelectric nanoparticles with rich grain boundaries and torsional strain on the surface is carried out according to the following steps:
[0006] 1. adding bismuth nitrate pentahydrate to a dilute nitric acid solution, and then stirring at room temperature until the solution becomes clear, to obtain a bismuth nitrate solution;
[0007] 2. adding manganese nitrate tetrahydrate and potassium permanganate to the bismuth nitrate solution, and then stirring at room temperature to obtain a metal precursor mixed solution;
[0008] 3. Add KOH solution to the metal precursor mixed solution until the solution color changes from colorless to black and the pH is 10-11 to obtain a reaction system. Stir the reaction system at room temperature, then heat it at 180°C-200°C for 16h-24h, and finally cool it to room temperature. Collect it by centrifugation, wash and dry it to obtain Bi 2 Mn 4 O 10 Nanoparticles.
[0009] The beneficial effects of the present invention are:
[0010] ① The present invention prepares a bismuth manganate ferroelectric nanocrystal with rich surface grain boundaries and torsional stress. This nanozyme has relatively good ferroelectric properties and can have a high ferroelectric response ability under ultrasonic conditions.
[0011] ② The prepared bismuth manganate nanocrystals exhibit excellent ferroelectric and piezoelectric properties. And under ultrasonic conditions, water and oxygen can be converted into hydrogen peroxide through a single-electron WOR process and a two-electron ORR process. This makes up for the problem of insufficient endogenous hydrogen peroxide in the tumor microenvironment. It provides a rich substrate reserve for subsequent enzymatic kinetic catalysis and can amplify the production of reactive oxygen species (ROS).
[0012] ③ Ultrasound has strong penetration into the human body and is non-destructive to normal tissues. Its penetration can reach 3cm to 5cm. Under ultrasonic conditions, bismuth manganate nanoparticles generate an enhanced internal electric field through ferroelectric polarization. Electrons and holes move to both sides of the material respectively, and water molecules and oxygen molecules undergo catalytic reactions on the surface of the material, producing more ROS. And under the unique conditions of TME, glutathione and NADPH can be consumed, inhibiting the production of GSH from the source, greatly reducing the GSH content in TME, and indirectly regulating the level of ROS. Due to the rich grain boundaries on the surface of bismuth manganate nanosheets, these grain boundaries as defects can also increase active sites and improve enzyme activity. Under acidic conditions, it exhibits excellent peroxidase activity and effectively converts hydrogen peroxide into active substances (hydroxyl radicals).
[0013] ④Bismuth manganate nanozymes can be used as magnetic resonance imaging contrast agents and CT contrast agents for real-time monitoring of tumor treatment process.
[0014] Therefore, the preparation method of the ultrasonically responsive bismuth manganate ferroelectric nanoparticles of the present invention, which are rich in grain boundaries and torsional strain on the surface, is simple, ultrasound has a deeper tissue penetration depth, and has multiple functions such as multi-modal imaging (including nuclear magnetic resonance and CT imaging) and treatment (ferroelectric catalysis and enzyme-catalyzed anti-tumor therapy). BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 Preparation of Bi for Example 1 2 Mn 4 O 10 Schematic diagram of the process of nanoparticles;
[0016] Figure 2 Bi prepared in Example 1 2 Mn 4 O 10 TEM imaging and high-resolution images of nanoparticles, a is a transmission electron microscope image, b is a locally enlarged high-resolution electron transmission image;
[0017] Figure 3 Bi prepared in Example 1 2 Mn 4 O 10 HRTEM images of nanoparticles, a is a locally enlarged high-resolution electron transmission image, and b is a fast Fourier transform (FFT) image;
[0018] Figure 4 The Bi prepared in Example 1 2 Mn 4 O 10 GPA analysis of HRTEM images of nanoparticles, a is the axial strain (ε yy ), b is the GPA image corresponding to the axial strain and shear strain quantified by GPA within the white box, and c is the shear strain (ε xy ) corresponding GPA image;
[0019] Figure 5 Bi prepared in Example 1 2 Mn 4 O 10 Elemental mapping of nanoparticles;
[0020] Figure 6 Bi prepared in Example 1 2 Mn 4 O 10 X-ray diffraction spectrum of nanoparticles;
[0021] Figure 7 Bi prepared in Example 1 2 Mn 4 O 10 Ferroelectric hysteresis loop of nanoparticles;
[0022] Figure 8 Bi prepared in Example 1 2 Mn 4 O 10 Piezoelectric amplitude and phase diagram of nanoparticles, 1 is the piezoelectric butterfly curve, 2 is the phase hysteresis loop spectrum;
[0023] Fig. 9 At 1.2W / cm 2 Under the conditions of 2 Mn 4 O 10 UV-visible absorption spectra of nanoparticles dispersed in an aqueous solution containing potassium titanium oxalate for 10 min, 1 for 2 min, 2 for 4 min, 3 for 6 min, 4 for 8 min, and 5 for 10 min;
[0024] Fig.10 are UV-visible absorption spectra corresponding to different concentrations of hydrogen peroxide, a is a UV-visible absorption spectra of different concentrations of hydrogen peroxide dispersed in potassium titanium oxalate solution, 1 is 0.625mM, 2 is 1.25Mm, 3 is 2.5mM, 4 is 5mM, 5 is 10mM, 6 is 20mM, b is a scatter plot of absorbance corresponding to hydrogen peroxide concentration;
[0025] Fig.11 Bi prepared in Example 1 under different sacrificial agent addition conditions 2 Mn 4 O 10 UV-visible absorption spectra of the mixed solution of nanoparticles and potassium titanium oxalate at different ultrasonic times, 1 is without any sacrificial agent, 2 is with silver nitrate, 3 is with tert-butanol, 4 is with methanol;
[0026] Fig.12 Bi prepared in Example 1 under ultrasonic and non-ultrasonic conditions 2 Mn 4 O 10 Effect of nanoparticles on the degradation of methylene blue, a is without ultrasound, b is at 1.2W / cm 2 Under low-frequency ultrasound conditions, 1 in a and b is 0 min, 2 is 2 min, 3 is 4 min, 4 is 6 min, and 5 is 8 min;
[0027] Fig.13 At 1.2W / cm 2 Under the action of ultrasound, Bi prepared in Example 1 2 Mn 4 O 10 Electron spin resonance spectra of nanoparticle dispersion (concentration 100 μg / mL) and water, 1 is water, 2 is Bi2 Mn 4 O 10 Nanoparticle dispersion;
[0028] Fig.14 Hydrogen peroxide (33.3 mM) and Bi 2 Mn 4 O 10 Ultraviolet absorption spectra of the color change reaction of the nanoparticle dispersion in 3,3',5,5'-tetramethylbenzidine (TMB) over time, 1 is 1 min, 2 is 2 min, 3 is 4 min, 4 is 6 min, 5 is 8 min, and 6 is 10 min;
[0029] Fig.15 For different concentrations of hydrogen peroxide and Bi 2 Mn 4 O 10 UV absorption spectra of the color change reaction of the nanoparticle dispersion in 3,3',5,5'-tetramethylbenzidine, the hydrogen peroxide concentrations of 1-4 are 4mM, 8mM, 16mM and 50mM respectively;
[0030] Fig.16 For different concentrations of hydrogen peroxide and Bi 2 Mn 4 O 10 The rate fitting curve of the color change reaction of nanoparticle dispersion in 3,3',5,5'-tetramethylbenzidine;
[0031] Fig.17 For different concentrations of hydrogen peroxide and Bi 2 Mn 4 O 10 Double reciprocal fitting curve of the color change reaction of nanoparticle dispersion in 3,3',5,5'-tetramethylbenzidine. DETAILED DESCRIPTION
[0032] Specific implementation method 1: This implementation method is a method for preparing ferroelectric nanoparticles with rich grain boundaries and torsional strain on the surface, which is carried out according to the following steps:
[0033] 1. adding bismuth nitrate pentahydrate to a dilute nitric acid solution, and then stirring at room temperature until the solution becomes clear, to obtain a bismuth nitrate solution;
[0034] 2. adding manganese nitrate tetrahydrate and potassium permanganate to the bismuth nitrate solution, and then stirring at room temperature to obtain a metal precursor mixed solution;
[0035] 3. Add KOH solution to the metal precursor mixed solution until the solution color changes from colorless to black and the pH is 10-11 to obtain a reaction system. Stir the reaction system at room temperature, then heat it at 180°C-200°C for 16h-24h, and finally cool it to room temperature. Collect it by centrifugation, wash and dry it to obtain Bi 2 Mn 4 O 10 Nanoparticles.
[0036] This embodiment achieves excellent ferroelectric and catalytic properties by designing a bismuth manganate nanoparticle with a surface rich in grain boundaries. Unlike point and line defects, grain boundaries not only enhance electrical properties but also create a stable strain field, which is critical for maintaining catalytic activity and structural integrity in the acidic tumor microenvironment (TME). By regulating the domain structure, grain boundaries and torsional strain can accelerate polarization switching, thereby improving the effectiveness of the material in sonodynamic therapy (SDT). In addition, the high active site density at the grain boundaries increases the H 2 O 2 production efficiency, further enhancing the generation of reactive oxygen species (ROS).
[0037] In this embodiment, bismuth nitrate is used as a bismuth source and manganese nitrate is used as a manganese source. A bismuth manganate ferroelectric nanoparticle with a surface rich in grain boundaries and torsional strain and an ultrasonic response is prepared by a hydrothermal method. The chemical formula is: Bi 2 Mn 4 O 10 .
[0038] The beneficial effects of this embodiment are:
[0039] ① In this embodiment, a bismuth manganate ferroelectric nanocrystal with rich surface grain boundaries and torsional stress is prepared. This nanozyme has relatively good ferroelectric properties and can have a high ferroelectric response ability under ultrasonic conditions.
[0040] ② The prepared bismuth manganate nanocrystals exhibit excellent ferroelectric and piezoelectric properties. And under ultrasonic conditions, water and oxygen can be converted into hydrogen peroxide through a single-electron WOR process and a two-electron ORR process. This makes up for the problem of insufficient endogenous hydrogen peroxide in the tumor microenvironment. It provides a rich substrate reserve for subsequent enzymatic kinetic catalysis and can amplify the production of reactive oxygen species (ROS).
[0041] ③ Ultrasound has strong penetration into the human body and is non-destructive to normal tissues. Its penetration can reach 3cm to 5cm. Under ultrasonic conditions, bismuth manganate nanoparticles generate an enhanced internal electric field through ferroelectric polarization. Electrons and holes move to both sides of the material respectively, and water molecules and oxygen molecules undergo catalytic reactions on the surface of the material, producing more ROS. And under the unique conditions of TME, glutathione and NADPH can be consumed, inhibiting the production of GSH from the source, greatly reducing the GSH content in TME, and indirectly regulating the level of ROS. Due to the rich grain boundaries on the surface of bismuth manganate nanosheets, these grain boundaries as defects can also increase active sites and improve enzyme activity. Under acidic conditions, it exhibits excellent peroxidase activity and effectively converts hydrogen peroxide into active substances (hydroxyl radicals).
[0042] ④Bismuth manganate nanozymes can be used as magnetic resonance imaging contrast agents and CT contrast agents for real-time monitoring of tumor treatment process.
[0043] Therefore, the preparation method of the ultrasonically responsive bismuth manganate ferroelectric nanoparticles with rich grain boundaries and torsional strain on the surface in this embodiment is simple, the ultrasound has a deep tissue penetration depth, and it has multiple functions such as multimodal imaging (including nuclear magnetic resonance, CT imaging) and treatment (ferroelectric catalysis and enzyme-catalyzed anti-tumor therapy).
[0044] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the concentration of the dilute nitric acid solution in step 1 is 0.2 mol / L to 0.5 mol / L. The rest is the same as specific implementation method 1.
[0045] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the volume ratio of the mass of bismuth nitrate pentahydrate described in step 1 to the dilute nitric acid solution is (8-10) mg:1 mL. Other aspects are the same as specific implementation method 1 or 2.
[0046] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: in step 1, stirring is performed at room temperature and a stirring speed of 300 rpm to 500 rpm for 5 to 10 minutes until the solution is clear. The rest is the same as specific embodiments 1 to 3.
[0047] Specific embodiment 5: This embodiment differs from Specific embodiments 1 to 4 in that: the mass ratio of manganese nitrate tetrahydrate described in step 2 to the volume ratio of bismuth nitrate solution is (8-10) mg:1 mL; the mass ratio of potassium permanganate described in step 2 to the volume ratio of bismuth nitrate solution is (0.5-0.8) mg:1 mL. Others are the same as Specific embodiments 1 to 4.
[0048] Specific implementation example 6: This implementation example is different from specific implementation examples 1 to 5 in that: in step 2, stirring is performed for 5 to 10 minutes at room temperature and a stirring speed of 300 to 500 rpm. The rest is the same as specific implementation examples 1 to 5.
[0049] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: in step 3, the KOH solution is added to the metal precursor mixed solution at a rate of 5 mL / min to 8 mL / min; the concentration of the KOH solution in step 3 is 2 mol / L to 4 mol / L. The rest is the same as specific embodiments 1 to 6.
[0050] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that: in step 3, the reaction system is stirred for 20 min to 30 min at room temperature and a stirring speed of 300 rpm to 500 rpm. The rest is the same as specific embodiments 1 to 7.
[0051] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: in step 3, the temperature is increased to 180° C. to 200° C. at a rate of 5° C. / min to 8° C. / min. The rest is the same as specific embodiments 1 to 8.
[0052] Specific embodiment 10: This embodiment is different from specific embodiments 1 to 9 in that the centrifugal collection and washing and drying described in step 4 are specifically carried out according to the following steps: centrifugation for 10 min to 15 min at a rotation speed of 6000 rpm to 8000 rpm, then washing with water and ethanol in sequence, and repeating the washing for multiple times, and finally vacuum drying overnight at a temperature of 60° C. to 65° C. The rest is the same as specific embodiments 1 to 9.
[0053] The following examples are used to verify the beneficial effects of the present invention:
[0054] Embodiment 1, combined with Figure 1 Specific instructions:
[0055] A method for preparing ferroelectric nanoparticles with rich grain boundaries and torsional strain on the surface is carried out according to the following steps:
[0056] 1. adding bismuth nitrate pentahydrate to a dilute nitric acid solution, and then stirring the solution for 5 minutes at room temperature and a stirring speed of 500 rpm / min to clarify the solution, thereby obtaining a bismuth nitrate solution;
[0057] The concentration of the dilute nitric acid solution is 0.5 mol / L; the mass ratio of the bismuth nitrate pentahydrate to the dilute nitric acid solution is 9 mg:1 mL
[0058] 2. adding manganese nitrate tetrahydrate and potassium permanganate to the bismuth nitrate solution, and then stirring for 10 minutes at room temperature and a stirring speed of 500 rpm / min to obtain a metal precursor mixed solution;
[0059] The mass ratio of the manganese nitrate tetrahydrate to the volume ratio of the bismuth nitrate solution is 8 mg:1 mL; the mass ratio of the potassium permanganate to the volume ratio of the bismuth nitrate solution is 0.7 mg:1 mL;
[0060] 3. Add KOH solution to the metal precursor mixed solution at a rate of 5 mL / min until the solution color changes from colorless to black and the pH is 11 to obtain a reaction system. Stir the reaction system for 30 min at room temperature and a stirring rate of 500 rpm / min, then heat to 180 ° C at a heating rate of 5 ° C / min, and heat at 180 ° C for 24 h. Finally, cool to room temperature, collect by centrifugation, wash and dry to obtain Bi 2 Mn 4 O 10 Nanoparticles;
[0061] The concentration of the KOH solution is 4 mol / L;
[0062] The centrifugal collection and washing and drying are specifically carried out according to the following steps: centrifugation at a rotation speed of 8000 rpm for 10 minutes, then washing with water and ethanol in sequence, and repeating the washing three times, and finally vacuum drying at a temperature of 60°C overnight.
[0063] Figure 1 Preparation of Bi for Example 1 2 Mn 4 O 10 Schematic diagram of the process of nanoparticles; as can be seen from the figure, after adjusting the pH value of the metal ion solution with KOH, a metal precursor is formed, and then Bi is formed after a hydrothermal reaction at 180°C for 24 hours. 2 Mn 4 O 10 Nanoparticles.
[0064] Figure 2 Bi prepared in Example 1 2 Mn 4 O 10 TEM imaging and high-resolution images of nanoparticles, a is the transmission electron microscope image, b is the locally enlarged high-resolution electron transmission image; it can be seen from the figure that Bi 2 Mn 4 O 10The nanoparticles are spindle-shaped and about 220 nm in size. HRTEM images show multiple grain boundaries and good surface crystallinity, with interplanar spacing corresponding to (211) and (121) planes.
[0065] Figure 3 Bi prepared in Example 1 2 Mn 4 O 10 HRTEM image of nanoparticles, a is a locally enlarged high-resolution electron transmission image, b is a fast Fourier transform (FFT) image; it can be seen from the figure that the prepared Bi 2 Mn 4 O 10 The nanoparticles contain large-angle grain boundaries, and the two adjacent spots in the FFT image reflect the existence of twisted grain boundaries.
[0066] To further quantify Bi 2 Mn 4 O 10 Strain distribution around grain boundaries in nanoparticles, using geometric phase analysis (GPA). Under lattice distortion, both shear strain and axial strain (which can be expressed as compressive strain or tensile strain) are generated at the grain boundaries.
[0067] Figure 4 The Bi prepared in Example 1 2 Mn 4 O 10 GPA analysis of HRTEM images of nanoparticles, a is the axial strain (ε yy ), b is the GPA image corresponding to the axial strain and shear strain quantified by GPA within the white box, and c is the shear strain (ε xy ) corresponding to the GPA image. 2 Mn 4 O 10 In nanoparticles, shear strain (ε xy ) alternate on both sides of the grain boundary, indicating that under the influence of shear force, the material's microstructure undergoes periodic local distortion at the grain boundary. These dislocations help to evenly distribute stress, promote stable domain wall motion, and have a positive effect on the ferroelectric response. In addition, Bi 2 Mn 4 O 10 Higher shear strain values (ε xy =9%), indicating that the material exhibits a stronger stress response under shear stress. yy = 15%) may improve the stability and uniformity of the material under external stress. 2 Mn 4 O 10The stress distribution in the nanoparticles leads to better ferroelectric stability and consistency, while showing a stronger response to shear stress.
[0068] Figure 5 Bi prepared in Example 1 2 Mn 4 O 10 Elemental mapping of nanoparticles; As can be seen from the figure, the prepared Bi 2 Mn 4 O 10 Bi, Mn and O elements are evenly distributed in the nanoparticles.
[0069] Figure 6 Bi prepared in Example 1 2 Mn 4 O 10 X-ray diffraction spectrum of nanoparticles; As can be seen from the figure, Bi 2 Mn 4 O 10 The peaks are located at 15.3°, 28.6°, 30.2°, and 14.5°, corresponding to Bi 2 Mn 4 O 10 Standard card JCPDS, No. 74-1096 (001), (121), (211) and (001) crystal planes. Figure 2 , Figure 5 and Figure 6 The results showed that Bi 2 Mn 4 O 10 Nanoparticles.
[0070] At room temperature and 7 kV, the Bi prepared in Example 1 was 2 Mn 4 O 10 Ferroelectric hysteresis loop test of nanoparticles. Figure 7 Bi prepared in Example 1 2 Mn 4 O 10 Ferroelectric hysteresis loop of nanoparticles. As shown in the figure, the Bi prepared in Example 1 2 Mn 4 O 10 The residual magnetization of the nanoparticles is 6.1 μC / cm 2 .
[0071] Figure 8 Bi prepared in Example 1 2 Mn 4 O 10 The piezoelectric amplitude and phase diagram of the nanoparticles, 1 is the piezoelectric butterfly curve, 2 is the phase hysteresis loop spectrum; it can be seen from the figure that Bi2 Mn 4 O 10 Nanoparticles 33 The value is 9mV / V, and the phase hysteresis loop spectrum is close to a phase transition of ≈180°, confirming that Bi 2 Mn 4 O 10 It has typical piezoelectric properties.
[0072] Detection Bi 2 Mn 4 O 10 Effect of nanoparticles on potassium titanium oxalate under ultrasonic conditions. First, 200 μg of Bi prepared in Example 1 was added. 2 Mn 4 O 10 The nanoparticles were dispersed in 2 mL of a pH 5 aqueous solution containing potassium titanium oxalate (the concentration of potassium titanium oxalate was 100 μg / mL). To avoid the effects of photodegradation, the entire experiment was conducted under light-shielded conditions. 2 The mixed solution was ultrasonicated with an ultrasonic probe under the condition of . 1 mL of solution was collected at different times of ultrasonication, and the supernatant was collected by centrifugation for UV absorption curve test, so as to evaluate the Bi 2 Mn 4 O 10 The effect of nanoparticles on potassium titanium oxalate under ultrasound, e.g. Fig. 9 shown.
[0073] Fig. 9 At 1.2W / cm 2 Under the conditions of 2 Mn 4 O 10 The UV-visible absorption spectra of nanoparticles dispersed in an aqueous solution containing potassium titanium oxalate for 10 minutes, 1 is 2 minutes, 2 is 4 minutes, 3 is 6 minutes, 4 is 8 minutes, and 5 is 10 minutes; it can be seen from the figure that with the increase of low-power ultrasonic irradiation time, the absorption peak of the UV-visible absorption spectrum at 415nm gradually increases. This shows that in a slightly acidic environment, Bi 2 Mn 4 O 10 Nanoparticles can produce hydrogen peroxide, an active oxygen species, under low-power ultrasonic irradiation, and the effect of hydrogen peroxide production is significantly improved as the ultrasonic irradiation time increases.
[0074] In order to quantify the hydrogen peroxide production corresponding to the absorbance of potassium titanium oxalate, 100 μL of hydrogen peroxide with different concentrations was mixed with 100 mL of potassium titanium oxalate solution with the same concentration (100 μg / mL) and subjected to UV absorption spectrum test. The linear relationship between hydrogen peroxide concentration and absorbance and the correlation coefficient were analyzed, as shown in Figure 2. Fig.10 shown.
[0075] Fig.10 Figure 1 is the UV-visible absorption spectra corresponding to different concentrations of hydrogen peroxide, a is the UV-visible absorption spectra of different concentrations of hydrogen peroxide dispersed in potassium titanium oxalate solution, 1 is 0.625mM, 2 is 1.25Mm, 3 is 2.5mM, 4 is 5mM, 5 is 10mM, 6 is 20mM, and b is a scatter plot of absorbance corresponding to hydrogen peroxide concentration. The correlation coefficient obtained by linear fitting is 0.99, indicating that there is a linear relationship between hydrogen peroxide concentration and potassium titanium oxalate absorbance.
[0076] Detect the pathway of hydrogen peroxide production. Methanol (10 mM), silver nitrate (100 μg / mL), and tert-butyl alcohol (100 μg / mL) were used as sacrificial agents to capture piezoelectric holes, piezoelectric electrons, and hydroxyl radicals generated during ultrasound. 2 Mn 4 O 10 The nanoparticle solution was mixed with 3 mL of potassium titanium oxalate solution to obtain a mixed solution. The potassium titanium oxalate and Bi 2 Mn 4 O 10 The nanoparticle concentration was 100 μg / mL. 2 The mixed solution was ultrasonicated with an ultrasonic probe under the condition of . 1 mL of solution was collected at different ultrasonic times, and the supernatant was collected by centrifugation for UV absorption curve test, thereby evaluating the Bi under different sacrificial agents. 2 Mn 4 O 10 The effect of nanoparticles' ability to produce hydrogen peroxide under ultrasound, e.g. Fig.11 shown.
[0077] Fig.11 Bi prepared in Example 1 under different sacrificial agent addition conditions 2 Mn 4 O 10UV-visible absorption spectra of the mixed solution of nanoparticles and potassium titanium oxalate at different ultrasonic times, 1 is without adding any sacrificial agent, 2 is adding silver nitrate, 3 is adding tert-butanol, and 4 is adding methanol. As can be seen from the figure, after adding silver nitrate, the hydrogen peroxide production decreased slightly, while after adding tert-butanol as a hydroxyl radical scavenger, the hydrogen peroxide production decreased significantly, especially after adding methanol, the hydrogen peroxide production was the lowest. This shows that the production of hydrogen peroxide is mainly related to the hole transfer process, and the hydroxyl radical as an intermediate product of the reaction also plays a decisive role in the production of hydrogen peroxide. It further proves that the ultrasonic hydrogen peroxide production process in this system is a single-electron process.
[0078] Study the Bi prepared in Example 1 under ultrasonic and non-ultrasonic conditions. 2 Mn 4 O 10 Effect of nanoparticles on the degradation of methylene blue. First, 200 μg of Bi prepared in Example 1 was added to 2 Mn 4 O 10 The nanoparticles were dispersed in 2 mL of an aqueous solution containing methylene blue at pH 5 (the concentration of methylene blue was 100 μg / mL). To avoid the influence of photodegradation, the entire experiment was carried out under light-proof conditions. 1 mL of solution was collected at different incubation times, and the supernatant was collected by centrifugation for UV absorption curve testing to evaluate the Bi reaction at different reaction times. 2 Mn 4 O 10 The effect of nanoparticles on methylene blue. 2 The mixed solution was ultrasonicated with an ultrasonic probe under the condition of , 1mL of solution was collected at different ultrasonic times, and the supernatant was collected by centrifugation for UV absorption curve test, so as to evaluate the Bi at different ultrasonic times. 2 Mn 4 O 10 Effect of nanoparticles on methylene blue under ultrasound.
[0079] Fig.12 Bi prepared in Example 1 under ultrasonic and non-ultrasonic conditions 2 Mn 4 O 10 Effect of nanoparticles on the degradation of methylene blue, a is without ultrasound, b is at 1.2W / cm 2 Under low-frequency ultrasound conditions, 1 in a and b is 0 min, 2 is 2 min, 3 is 4 min, 4 is 6 min, and 5 is 8 min. As can be seen from the figure, under no ultrasound conditions, due to the peroxidase activity of the material, Bi 2 Mn 4 O 10Nanoparticles can produce hydroxyl radicals in hydrogen peroxide solution and have significant MB degradation ability. However, under ultrasonic conditions, the MB degradation effect is very limited, indicating that hydroxyl radicals are quickly produced and consumed as intermediates during the ultrasonic process, so it is difficult to be captured and degraded by MB. This further proves that the single-electron production of hydrogen peroxide is the main process during the ultrasonic process.
[0080] Fig.13 At 1.2W / cm 2 Under the action of ultrasound, Bi prepared in Example 1 2 Mn 4 O 10 Electron spin resonance spectra of nanoparticle dispersion (concentration 100 μg / mL) and water, 1 is water, 2 is Bi 2 Mn 4 O 10 Nanoparticle dispersion; As can be seen from the figure, no obvious hydroxyl radical signal peak was observed when ultrasonic was applied to water alone, while Bi 2 Mn 4 O 10 After ultrasound, the nanoparticle dispersion showed a signal peak of hydroxyl radical active oxygen species, proving the ability of nanoparticle materials to produce active oxygen species under low-power ultrasonic irradiation.
[0081] Bi 2 Mn 4 O 10 Method for testing the enzyme-like activity of nanoparticles: Bi prepared in Example 1 2 Mn 4 O 10 The nanoparticles were added to water to obtain 3 mL of Bi with a concentration of 100 μg / mL. 2 Mn 4 O 10 The nanoparticle dispersion was then added with 100 μL of 3,3',5,5'-tetramethylbenzidine containing hydrogen peroxide to react, thus completing the Bi 2 Mn 4 O 10 Nanoparticle-based enzyme activity assays, such as Figures 14 to 17 .
[0082] Fig.14 Hydrogen peroxide (33.3 mM) and Bi 2 Mn 4 O 10The ultraviolet absorption spectrum of the color change reaction of the nanoparticle dispersion in 3,3',5,5'-tetramethylbenzidine (TMB) over time, 1 is 1min, 2 is 2min, 3 is 4min, 4 is 6min, 5 is 8min, and 6 is 10min. It can be seen from the figure that as the reaction time increases, the characteristic peak absorbance of TMB at 652nm increases, indicating that more and more hydroxyl radicals are generated.
[0083] Fig.15 For different concentrations of hydrogen peroxide and Bi 2 Mn 4 O 10 Ultraviolet absorption spectra of the color change reaction of the nanoparticle dispersion in 3,3',5,5'-tetramethylbenzidine, the hydrogen peroxide concentrations of 1-4 are 4mM, 8mM, 16mM and 50mM respectively. As can be seen from the figure, the active oxygen content in the mixed solution increases with the increase of hydrogen peroxide concentration and changes linearly with time.
[0084] Fig.16 For different concentrations of hydrogen peroxide and Bi 2 Mn 4 O 10 The rate fitting curve of the color change reaction of the nanoparticle dispersion in 3,3',5,5'-tetramethylbenzidine. As can be seen from the figure, the reaction rate and substrate concentration fit well, and the corresponding Michaelis-Menten equation is obtained.
[0085] Fig.17 For different concentrations of hydrogen peroxide and Bi 2 Mn 4 O 10 The double reciprocal fitting curve of the color change reaction of nanoparticle dispersion in 3,3',5,5'-tetramethylbenzidine. 2 Mn 4 O 10 The maximum reaction rate of hydrogen peroxide catalyzed by nanoparticles is 7.6×10 -8 Ms -1 , the Michaelis constant is 8.03mM.
Claims
1. A method for preparing ferroelectric nanoparticles with rich grain boundaries and torsional strain on the surface, characterized in that It is carried out in the following steps:
1. adding bismuth nitrate pentahydrate to a dilute nitric acid solution, and then stirring at room temperature until the solution becomes clear, to obtain a bismuth nitrate solution; 2. adding manganese nitrate tetrahydrate and potassium permanganate to the bismuth nitrate solution, and then stirring at room temperature to obtain a metal precursor mixed solution; 3. Add KOH solution to the metal precursor mixed solution until the solution changes from colorless to black and the pH is 10-11 to obtain a reaction system. Stir the reaction system at room temperature, then heat it at 180°C-200°C for 16h-24h, and finally cool it to room temperature. Collect it by centrifugation, wash and dry it to obtain Bi2Mn4O 10 Nanoparticles.
2. The method for preparing ferroelectric nanoparticles having a surface rich in grain boundaries and torsional strain according to claim 1, characterized in that The concentration of the dilute nitric acid solution described in step 1 is 0.2 mol / L to 0.5 mol / L.
3. The method for preparing ferroelectric nanoparticles having a surface rich in grain boundaries and torsional strain according to claim 2, characterized in that The volume ratio of the mass of bismuth nitrate pentahydrate described in step 1 to the dilute nitric acid solution is (8-10) mg:1 mL.
4. The method for preparing ferroelectric nanoparticles having a surface rich in grain boundaries and torsional strain according to claim 1, characterized in that In step 1, the mixture is stirred at room temperature and a stirring speed of 300 rpm to 500 rpm for 5 to 10 minutes until the solution is clear.
5. The method for preparing ferroelectric nanoparticles with rich grain boundaries and torsional strain on the surface according to claim 1, characterized in that The mass ratio of manganese nitrate tetrahydrate described in step 2 to the volume ratio of bismuth nitrate solution is (8-10) mg:1 mL; the mass ratio of potassium permanganate described in step 2 to the volume ratio of bismuth nitrate solution is (0.5-0.8) mg:1 mL.
6. The method for preparing ferroelectric nanoparticles with rich grain boundaries and torsional strain on the surface according to claim 1, characterized in that In step 2, stirring is performed for 5 min to 10 min at room temperature and a stirring speed of 300 rpm to 500 rpm.
7. The method for preparing ferroelectric nanoparticles with rich grain boundaries and torsional strain on the surface according to claim 1, characterized in that In step 3, the KOH solution is added to the metal precursor mixed solution at a rate of 5 mL / min to 8 mL / min; the concentration of the KOH solution in step 3 is 2 mol / L to 4 mol / L.
8. The method for preparing ferroelectric nanoparticles with rich grain boundaries and torsional strain on the surface according to claim 1, characterized in that In step 3, the reaction system is stirred for 20 min to 30 min at room temperature and a stirring speed of 300 rpm to 500 rpm.
9. The method for preparing ferroelectric nanoparticles with rich grain boundaries and torsional strain on the surface according to claim 1, characterized in that In step 3, the temperature is increased to 180°C to 200°C at a heating rate of 5°C / min to 8°C / min.
10. The method for preparing ferroelectric nanoparticles with rich grain boundaries and torsional strain on the surface according to claim 1, characterized in that The centrifugal collection and washing and drying described in step 4 are specifically carried out according to the following steps: centrifuge for 10min to 15min at a rotation speed of 6000rpm to 8000rpm, then wash with water and ethanol in turn, and repeat the washing several times, and finally vacuum dry overnight at a temperature of 60℃ to 65℃.
